Application of the Principle Rule of Reason to the Determination of Airline Ticket Prices in Business Competition Practices - Maudy Miranda; Elisatris Gultom; Deviana Yuanitasari (PATTIMURA Legal Journal, 2025)
Introduction: Business competition often drives companies to engage in unfair practices, including violations of the rule of reason principle, where market dominance is achieved through cartel-like behavior. This study focuses on analyzing how this principle applies to airline ticket pricing, particularly under Law Number 5 of 1999 concerning Monopoly Practices and Unfair Business Competition in Indonesia. Purposes of the Research: This research aims to analyze the application of the rule of reason principle in airline ticket pricing and assess whether airlines' pricing practices comply with Law Number 5 of 1999, focusing on a case involving seven airlines accused of anti-competitive behavior. Methods of the Research: This research uses normative legal research methods, relying on secondary data collected through literature studies. The analysis focuses on interpreting Law Number 5 of 1999, specifically Article 5, to determine whether airline pricing practices, including those of seven airlines under investigation, violate the rule of reason principle and constitute unfair competition. Results Main Findings of the Research: This research demonstrates that a violation under the rule of reason principle demands rigorous evaluation of market effects. The case involving seven airlines uncovered a price-fixing scheme in breach of Article 5 of Law No. 5 of 1999. By restricting routes and low-cost ticket availability, the conduct significantly eroded consumer welfare and disrupted the integrity of competitive market structures.